Pemetaan Groundwater Recharge Potential (GRP) Dengan Pendekatan SIG (Sistem Informasi Geografis), Studi Kasus Daerah Aliran Sungai Cibeusi, Kawasan Jatinangor, Kabupaten Sumedang - Bayu Nugraha (JOURNAL OF APPLIED SCIENCE (JAPPS), 2023)
Jatinangor District is located on the west side of Sumedang Regency which is directly adjacent to Bandung Regency. In accordance with Regional Regulation No. 4 of 2018 concerning the Sumedang Regency Spatial Planning, Jatinangor District is a priority area for higher education areas and urban settlements. Urbanization and population growth that occur can affect the frequency of groundwater use which continues to increase [1]. The groundwater table in the Jatinangor area and its surroundings has decreased due to the conversion of the recharge zone function which has an impact on reducing the area of the recharge zone [2]. The purpose of this research activity is to determine the potential of the recharge zone in the Cibeusi Watershed in Jatinangor District, Sumedang Regency. Determining the groundwater recharge potential (GRP) in research activities carried out using the GIS approach and the AHP method. AHP is part of the Multi-Criteria Decision Making (MCDM) method which was developed into an efficient and reliable method for making decisions in GIS analysis [3], [4]. The results showed that the weighted values of the five parameters used resulted in five different class categories. low category with a percentage of 5.5%, moderate category with a percentage of 54.5%, good category with a percentage of 34.5% and excellent category with a percentage of 4.6%. The best groundwater catchment area potential of 4.6% of the total Cibeusi watershed area is in the Cileunyi Wetan area with an infiltration zone elevation ranging from 837.5-887.5m asl